ANALISIS WACANA BERITA “KABAR WENGI” DI TATV - Kinasih Yuliastuti; Bayu Indrayanto (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2022)
Discourse analysis of the news "Kabar Wengi" on TATV is a study in the field of discourse, by examining grammatical and lexical aspects. The type of research used is descriptive qualitative. The research data needed in the research is written data in the form of News Discourse "Kabar Wengi" on TATV. Writing data was obtained from the written source of News Discourse "Kabar Wengi" on TATV. The source of the data in this study is the source of written data in the form of "Kabar Wengi" News Discourse on TATV. Collecting data in this study using the see method. The basic technique used is tapping technique, while the advanced technique that the writer uses is note-taking technique. The method used in analyzing the data is the distributional method. The grammatical aspects of discourse found are persona reference, demonstrative reference, substitution, ellipsis, and conjunction. The most dominant grammatical aspect of discourse tool is persona reference. The tools/tools of discourse in the lexical aspect are repetition (repetition), synonymy (word equivalents), antonyms (meaning opposition), collocations (adjunctions). The most dominant tool for lexical aspect of discourse is collocation (adjunction).